1996
DOI: 10.1063/1.361118
|View full text |Cite
|
Sign up to set email alerts
|

Charge trapping in dry and wet oxides on N-type 6H–SiC studied by Fowler–Nordheim charge injection

Abstract: Metal-oxide-semiconductor capacitors fabricated by dry and wet oxidation at 1150 °C of n-type 6H–SiC exhibit a drastic negative charging during Fowler–Nordheim charge injection. This charging strongly depends on the fabrication conditions of the samples. The densities of interface states and oxide charges can be significantly reduced by a postoxidation anneal in Ar for as long as 60 min. A large part of the charge appears to be trapped at the interface. These charges are released from the traps by illumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The precursors to these electron traps may not be charged during pre-irradiation characterization when the Fermi level sweeps through the band gap, but become charged due to ionizing radiation. Earlier studies have reported interface trap buildup at non-nitrided SiO /SiC interfaces resulting from electron injection via photo and Fowler-Nordheim methods [21]- [24]. A significant density of acceptor states was observed at the SiO /SiC interface after electron injection as compared to SiO /Si [21], [23].…”
Section: A Fundamental Band Gap and Interlayer Differences In Sio /Smentioning
confidence: 94%
“…The precursors to these electron traps may not be charged during pre-irradiation characterization when the Fermi level sweeps through the band gap, but become charged due to ionizing radiation. Earlier studies have reported interface trap buildup at non-nitrided SiO /SiC interfaces resulting from electron injection via photo and Fowler-Nordheim methods [21]- [24]. A significant density of acceptor states was observed at the SiO /SiC interface after electron injection as compared to SiO /Si [21], [23].…”
Section: A Fundamental Band Gap and Interlayer Differences In Sio /Smentioning
confidence: 94%
“…Both Ar anneal performed at growth temperature and re-oxidation at lower temperatures (e.g. 900 • C) have indeed proven to slightly reduce the amount of deep states [40,129]. This can be explained by the removal of excess carbon without additional oxide formation, as corresponding atomic configurations yield defects populating interface states toward the middle of the gap.…”
Section: Argon Annealmentioning
confidence: 99%
“…Both Ar anneal performed at growth temperature and re-oxidation at lower temperatures (e.g. 900 • C) have indeed proven to slightly reduce the amount of deep states [40,129]. This can be explained by the removal of excess carbon without additional oxide formation, as corresponding atomic configurations yield defects populating interface states toward the middle of the gap.…”
Section: Argon Annealmentioning
confidence: 92%